Analisis Hadis Keutamaan Ilmu dalam Konteks Pendidikan Islam - Abdullah Fauzan, Muhammad; Qurota A’yun, Amanah; Nur Azizah, Alfi; Abbas, Ngatmin (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
This study aims to examine the concept of seeking knowledge and its virtues in Islam based on the hadiths of the Prophet Muhammad (PBUH). The background of this research lies in the significance of knowledge in Islam, not only as a means of understanding religion but also as a foundation for addressing the challenges of contemporary developments. In this context, seeking knowledge is seen as an act of worship that provides great benefits to individuals and society. This research employs a qualitative method with a descriptive approach, collecting data from literature reviews of relevant hadiths and thematic analysis related to the virtues of knowledge in Islam. The findings indicate that seeking knowledge has various virtues, both in this world and the hereafter. The hadiths of the Prophet Muhammad (PBUH) explain that knowledge is a light that illuminates darkness, a path to paradise, and elevates one's status in the eyes of Allah SWT and society. Furthermore, seeking knowledge can bring prosperity, advance civilization, and serve as a continuous charity (sadaqah jariyah) whose rewards continue to flow. In the modern era, the relevance of the teachings on seeking knowledge is increasingly vital in encouraging Muslims to keep learning, innovating, and contributing positively in various fields of knowledge. Therefore, this study emphasizes that the hadiths on seeking knowledge provide a strong foundation for Muslims to continuously pursue and apply knowledge as a form of worship and social contribution. Seeking knowledge is not only an obligation but also a source of honor that provides lasting benefits for individuals and society.